Low energy availability surrogates in a sample of national team mexican athletes - Ayala-Guzmán, C. I.; Castillo-Rosales, I.; Silva-Quiroz, V.; Nájera-Medina, O.; Ortiz-Hernández, L. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Low energy availability should be directly evaluated, but it has also been measured through low energy availability surrogates (LEAS). The aim of this study was to identify the prevalence of LEAS in a sample of National Team Mexican athletes during pre-competitive stage, and to analyze differences of surrogates according to sex and sport disciplines. Athletes affiliated with the Mexican Olympic Committee were recruited. A convenience sample of 90 athletes participated in the study. Fifteen sport disciplines were classified into weight-sensitive sports (WSS) and no-weight-sensitive sports (NWSS). Three questionnaires were applied to identify risk eating behaviors (REB) and LEAS, and the following categories were created: REB, injuries and illness, dizziness, cold sensitivity, gastrointestinal and menstrual functioning. Descriptive analyzes, Student`s T-tests and Chi-squared tests were performed. 1.1-51.7% of participants showed some LEAS, while 45.6% of women had some menstrual dysfunction. There were no differences of LEAS according to sex of participants (p>0.050). Nevertheless, WSS showed higher rates of REB, illness, and dizziness (p<0.050). Interestingly, NWSS showed higher rates of constipation (p<0.050). There were no differences in menstrual function between women in WSS and NWSS (p>0.050). Sports disciplines` differences of LEAS were identified. Nutritional counseling can be used to avoid health acute or chronic consequences of low energy availability and relative energy deficiency in sport.